2023
DOI: 10.3389/fcimb.2022.1106369
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired antibodies to gametocyte antigens are associated with reduced transmission of Plasmodium vivax gametocytes to Anopheles arabiensis mosquitoes

Abstract: Naturally acquired antibodies may reduce the transmission of Plasmodium gametocytes to mosquitoes. Here, we investigated associations between antibody prevalence and P. vivax infectivity to mosquitoes. A total of 368 microscopy confirmed P. vivax symptomatic patients were passively recruited from health centers in Ethiopia and supplemented with 56 observations from asymptomatic P. vivax parasite carriers. Direct membrane feeding assays (DMFA) were performed to assess mosquito infectivity; for selected feeds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…It seems that neither the breadth nor the intensity of antibody responses against individual Pvs25, Pvs28, and Pvs230 antigens could explain the TBI. While the antibody titers against 3 antigens strongly correlated—as noted in a recent study by Tebeje et al [ 16 ], where strong correlations were seen among different antigens (including P vivax blood- and sexual-stage antigens)—some high-blocking, strain-transcending, and IgG-dependent plasma samples (eg, VYBN-020 and VTTY-119) had relatively lower MFI values vs all 3 antigens. It is challenging to determine the mechanisms of naturally acquired TBI.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It seems that neither the breadth nor the intensity of antibody responses against individual Pvs25, Pvs28, and Pvs230 antigens could explain the TBI. While the antibody titers against 3 antigens strongly correlated—as noted in a recent study by Tebeje et al [ 16 ], where strong correlations were seen among different antigens (including P vivax blood- and sexual-stage antigens)—some high-blocking, strain-transcending, and IgG-dependent plasma samples (eg, VYBN-020 and VTTY-119) had relatively lower MFI values vs all 3 antigens. It is challenging to determine the mechanisms of naturally acquired TBI.…”
Section: Discussionsupporting
confidence: 62%
“…The results suggest that there could be unidentified transmission-blocking vaccine (TBV) candidates. In the case of P vivax , a recent study revealed that antibodies against Pvs47, Pvs230, Pvs25, and PvHAP2 were associated with naturally acquired TBI [ 16 ]. In addition to these antigens, Pvs28 has been considered a promising TBV candidate [ 17 ], although the naturally acquired TBI against Pvs28 has never been investigated.…”
mentioning
confidence: 99%
“…Until now, the effective method for identifying potential candidates for P . vivax vaccines has been through studies of naturally acquired immunity in endemic populations [ 12 ] or in silico analysis and computational screening [ 13 ]. Besides, chimeric P .…”
Section: Introductionmentioning
confidence: 99%